Analysis of Earth Dam Design Problems under Confidence Theory Applied to PhuNinh Main Dam in Quang Nam - Quang Hung Nguyen, Lan Huong Nguyen, Van Quan Tran (International Journal of Advanced Science and Technology, 2020)
The current application of deterministic method in irrigation works safety assessment in Vietnam made it impossible to qualify confidence of works and impact of random variables on the works’ safety then have appropriate structural solutions. Under this research level II random design method has been applied in development of two dam safety problems for the main dam of PhuNinh reservoir in Quang Nam. Problem 1 (direct problem): assessing the confidence of PhuNinh main dam. Problem 2 (reverse problem): determining the size of earth dam according to standard confidence. The problems are closely related each to other: the analysis of the safety probability of the main dam, the impact of break-down mechanisms on dam safety and the effects of random variables on break-down mechanisms and the main dams as mentioned in Problem 1. The research will allocate the standard confidence by individual breakdown mechanism and take iteration to determine the size of the main dam according to the confidence standards. The confidence calculations for PhuNinh main dam showed that: in case of operation, the dam is likely to be in trouble due to water overtopping or downstream slope slides. Keywords: problem tree, confidence function, standard confidence, random variable, dam safety, overtopping.